The Relationship Between Digital Information Exposure and Social Stigma in People with Mental Disorders in Rural Areas Based on Traditional Culture - Stefani Chairunisa Kurniawati; Sifa Fauziah; Sri Kurnia Dewi (Al-Hijrah Indonesia, 2026)
Background: Social stigma toward people with mental disorders (PMD/ODGJ) remains prevalent in rural communities, where traditional cultural beliefs often reinforce negative perceptions. Limited exposure to evidence-based digital health information may exacerbate stigma by hindering accurate mental health literacy. Objective: This study aimed to examine the relationship between digital information exposure and social stigma toward PMD in a traditional rural setting. Methods: A quantitative cross-sectional study was conducted in Nyalindung Village, Cianjur Regency, involving 109 community members selected via purposive sampling. Digital information exposure was measured using the eHealth Literacy Scale (eHEALS), and social stigma was assessed using the Perceived Devaluation and Discrimination Scale (PDDS). Data were analyzed using descriptive statistics and the Chi-Square test (α = 0.05). Results: The majority of respondents reported low digital information exposure (52.3%), and 78.9% exhibited high social stigma toward PMD. Statistical analysis revealed a significant relationship between digital information exposure and social stigma (p < 0.001), with lower exposure strongly associated with higher stigma levels. Conclusion: Limited exposure to digital mental health information is significantly associated with elevated social stigma in traditional rural communities. Integrating culturally sensitive, digital-based mental health literacy interventions into primary healthcare and community outreach programs is recommended to reduce stigma and foster inclusive support systems.